Comparison of Surveillance of Acute Respiratory Tract Infections and Circulation of Respiratory Viruses in COVID-19 Patients in Germany and Egypt from 2020 to 2022: A Literature Review - chutzpah naura ardis (Faculty of Medicine - Universitas Pembangunan Nasional Veteran Jawa Timur, 2025)
Global surveillance patterns for respiratory diseases have changed due to the COVID-19 pandemic. Examples of countries that have implemented surveillance strategies adapted to the current situation are Germany and Egypt. Both countries have implemented adaptive surveillance strategies despite differences in their healthcare systems and epidemiological challenges. This literature review was conducted using electronic data sources obtained from various health websites, such as PubMed, Google Scholar, and ScienceDirect. This literature review used the PICO approach to describe the population of patients with acute respiratory diseases, adaptive surveillance system interventions, comparisons between data measurements taken before and during the Covid-19 pandemic, and results that included significant infection and mortality rates. The results of the study show that non-pharmaceutical interventions were successful in reducing the circulation of respiratory viruses in Germany, while in Egypt, an adaptive surveillance system was successful in detecting patterns of SARS-CoV-2 and influenza virus spread. These findings emphasize the importance of adaptive and responsive surveillance systems and effective interventions in the context of a pandemic. Global surveillance patterns for respiratory diseases have changed due to the COVID-19 pandemic. Examples of countries that have implemented surveillance strategies adapted to the current situation are Germany and Egypt. Both countries have implemented adaptive surveillance strategies despite differences in their healthcare systems and epidemiological challenges. This literature review was conducted using electronic data sources obtained from various health websites, such as PubMed, Google Scholar, and ScienceDirect. This literature review used the PICO approach to describe the population of patients with acute respiratory diseases, adaptive surveillance system interventions, comparisons between data measurements taken before and during the Covid-19 pandemic, and results that included significant infection and mortality rates. The results of the study show that non-pharmaceutical interventions were successful in reducing the circulation of respiratory viruses in Germany, while in Egypt, an adaptive surveillance system was successful in detecting patterns of SARS-CoV-2 and influenza virus spread. These findings emphasize the importance of adaptive and responsive surveillance systems and effective interventions in the context of a pandemic.